Technology Education in New Zealand: The connected curriculum - O’Sullivan, Gary (Design and Technology Education: An International Journal, 2010)
This paper aims to identify what actually takes place when policy directives bring together Technology Education, Enterprise Education, and the wider Community Partnerships. Since the introduction of a national technology curriculum to New Zealand schools in 1999 there has been little critique as to the intentions of the curriculum. In late 2005 a Ministry of Education two-year Education for Enterprise (E4E) project was contracted to run a professional development programme with a group of 16 schools, to examine ways in which teachers’ capability to include education for enterprise can be developed. Specific focus was to be on technology education and the fostering of links with the wider community. This paper will introduce research carried out to analyse the professional development programme and look at the impact it has had on classroom practice with consideration given to the ideologies behind the initiatives. Models of implementation will be identified and exemplars of real practice in the primary classroom will be highlighted. Attempts to align technology and enterprise education will be explored and an argument for technology education making a real difference will be put forward. The paper highlights these key factors: • The nature of a creative connected curriculum; • Practice in primary technology education; • Tensions between reality and ideology; • Fourth generation evaluation.